Metode Jarimatika Mempengaruhi Kemampuan Berhitung Perkalian Siswa Kelas II SDN Banjarbanggi 2 - Nabilla Nughta Putri; Anwas Mashuri; Ririn Setyowati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to identify the impact of the Jarimatika method on the multiplication skills of 2nd-grade students at Banjarbanggi 2 Elementary School. The Jarimatika method is a mathematics teaching technique that uses fingers as aids, making it easier for students to understand multiplication concepts. This research employs a quantitative approach with a one-group pre-test and post-test design. The sample consists of 16 students, and data were collected through tests. Data analysis included prerequisite tests, such as the normality test, and hypothesis testing using paired sample t-tests with SPSS 24. The normality test prerequisite is considered normal if the sig value is > 0.05. The results indicate that the Jarimatika method has an impact, as evidenced by a significant improvement in students' multiplication skills after being taught using the Jarimatika method, shown by the paired sample t-test result with a sig value of 0.000 < 0.05. The use of this method has a significant impact, improving the multiplication skills of 2nd-grade students at Banjarbanggi 2 Elementary School. The Jarimatika method can create a more enjoyable learning process and enhance students' arithmetic skills.